EFEKTIVITAS ANALGETIK KRIM TIPE M/A EKSTRAK ETANOL DAUN RANDU (Ceibapentandra (L) Gaertn) PADA HEWAN UJI MENCIT JANTAN - Setya Enti Rikomah; Devi Novia; Muhammad Fadhly (Oceana Biomedicina Journal, 2022)
Randu plant leaves (Ceiba pentandra (L) Gaertn) are commonly used in traditional medicine, one of which is an analgesic with secondary metabolites which are thought to be analgesics, namely flavonoids. The purpose of this study was to determine the analgesic effectiveness of the ethanol extract cream of randu leaves (Ceiba pentandra (L) Gaertn) in white male mice (Mus musculus). The research on the analgesic effectiveness of the ethanol extract cream of randum leaves used the hot plate method and used male white mice as the experimental animal media. The soles of the hind legs of the mice were heated over hot plated with a temperature of 550C then the test animals were given the treatment which was divided into 5 treatment groups, namely positive control (Conterpain cream), negative control (F0), F1 (10%), F2 (15%), F3 (20%) and 1 normal group. The response of mice was calculated every 30 minutes in 120 minutes. The data obtained were analyzed using the one-way ANOVA statistical test followed by the Duncan test with a confidence level of 99%. The results of the one-way ANOVA test showed that there were significant differences between treatment groups (0.00 <0.05). The results of the Duncan test showed that the group that provided the best analgesic effectiveness was F2 (15%) but not better than Positive Control.